Pengaruh Kesenjangan Digital Terhadap Pembangunan Pedesaan di Desa Sumber Rezeki Karang Agung Ilir Kabupaten Banyuasin - Islamy, Diah Putri; Sutinah, Sutinah; Ivana, Ivana; MK, Samsul (@-Publik: Jurnal Administrasi Publik, 2026)
The digital divide is an inequality in internet access in a region, while rural development itself is a sustainable development in terms of community welfare. The purpose of this study is to determine how much influence the digital divide has on rural development in the Sumber Rejeki village, Karang Agung Ilir sub-district, Banyuasin Regency. This researcher took the research location in the Sumber Rejeki village, Karang Agung Ilir sub-district, Banyuasin Regency, Palembang, where in this village it is still difficult to access the internet and the infrastructure in the village is inadequate. The author conducted a quantitative research method using a sample size of 150 people generated from the Slovin formula. The method in collecting data for this study is offline in the form of a questionnaire survey to the community in the Sumber Rejeki village, the data collection method in this study is using the normality test, simple regression linearity test, product moment correlation hypothesis test. The results of this study indicate that there is a positive and significant influence between the digital divide and rural development and it can be seen that the r value = 0.333 is greater than the p value <0.05. So it can be concluded that the influence of the digital divide on rural development has a positive and significant influence, so Ha is accepted and H0 is rejected.